Below the poverty line and non-communicable diseases in Kerala: The Epidemiology of Non-communicable Diseases in Rural Areas (ENDIRA) study. (6th May 2015) - Menon, Jaideep; Vijayakumar, N.; Joseph, Joseph K.; David, P.C.; Menon, M.N.; Mukundan, Shyam; Dorphy, P.D.; Banerjee, Amitava
Abstract: Introduction: India carries the greatest burden of global non-communicable diseases (NCDs). Poverty is strongly associated with NCDs but there are few prevalence studies which have measured poverty in India, particularly in rural settings. Methods: In Kerala, India, a population of 113, 462 individuals was identified. The "Epidemiology of Non-communicable Diseases in Rural Areas" (ENDIRA) study was conducted via ASHAs (Accredited Social Health Activists). Standardised questionnaires were used in household interviews of individuals ≥ 18 years during 2012 to gather sociodemographic, lifestyle and medical data for this population. The Government of Kerala definition of "the poverty line" was used. The association between below poverty line (BPL) status, NCDs and risk factors was analysed in multivariable regression models. Results: 84, 456 adults were included in the analyses (25.4% below the poverty line). The prevalence of NCDs was relatively common: myocardial infarction (MI) 1.4%, stroke 0.3%, respiratory diseases 5.0%, and cancer 1.1%. BPL status was not associated with age (p = 0.96) or gender (p = 0.26). Compared with those above the poverty line (APL), the BPL group was less likely to have diabetes, hypertension or dyslipidaemia (p < 0.0001), and more likely to smoke (p < 0.0001). Compared with APL, BPL was associated with stroke (OR 1.33, 1.04–1.69; p = 0.02) and respiratory disease (OR 1.23, 1.15–1.32; p < 0.0001) in multivariable analyses, but not MI or cancer. Conclusions: In rural Kerala, BPL status was associated with stroke and respiratory diseases, but not with MI and cancer although it was associated with smoking status, compared with above poverty line status.